Teaching the Environmental Science Education in the 21st-Century - Bacolod, Donnalyn (International Journal of Scientific Research and Management (IJSRM), 2021)
The school should reflect the real world. It should serve as the training ground for students to prepare in the actual workplace. The context in which courses are taught and learned has changed tremendously throughout the years. The advent of technology, the innovations in teaching, the demands of society, and the past and emerging environmental issues contributed to these changes. Environmental science is commonly an underestimated course as compared to others despite its critical role in environmental sustainability, community, and solving climate change-related problems. Students show less appreciation of its importance and difficulty in learning and applying its concepts to reality. The way that Environmental science courses should be more like the reality. As such, a new paradigm is needed to address these things to prepare students once they have embarked in their actual workplace.  A meaningful learning that is non-fragmented, dynamic, adaptive, technology-supported, flexible, future work-ready, and enhances critical thinking is imperative. Though there are already existing multiple frameworks in teaching environmental science, a new framework that offers students an opportunity to build and empower students’ learning ability through effective syntax is crucial in today’s era.